Prevention of Postoperative Events following Reversal with Sugammadex or Neostigmine (the P-PERSoN Trial): Pilot Data Following Early Termination of a Prospective, Blinded, Randomised Trial - Benjamin Olesnicky; Matthew Doane; Clare Farrell; Greg Knoblanche; Anthony Delaney (Anesthesiology Research and Practice)
Background. Residual paralysis following anaesthesia is common and can lead to postoperative morbidity. While sugammadex has been shown to be effective in minimising residual paralysis, uncertainty exists as to whether its use reduces any associated morbidity. We designed this trial to determine if the use of sugammadex for the reversal of intraoperative aminosteroid neuromuscular blockade results in improvements in postoperative pulmonary complications, complications in the recovery unit, postoperative nausea and vomiting, and patient satisfaction, when compared to reversal with neostigmine. Methods. A prospective, double-blind, randomised controlled trial in adult patients admitted for surgical operations at two Australian hospitals between December 2018 and March 2019 was performed comparing the reversal of neuromuscular paralysis using sugammadex 2 mg/kg versus neostigmine 50mcg/kg. Statistical analysis of continuous data was performed using two tailed t-tests, with categorical and ordinal data being assessed by chi-squared analysis. Results. The trial was terminated due to a combination of resource constraints and the 2019 novel coronavirus disease (COVID-19) pandemic. Of 51 patients screened, 33 were eligible for participation and 30 subsequently recruited and randomised. All patients received the intended treatment allocated. Data for the primary outcome was obtained in all patients. There was no difference in the rates of postoperative pulmonary complications between the sugammadex and neostigmine groups (0% (0/19) vs 9% (1/11) RR 5.0 (95% CI 0.22–113) p=0.37. There was no difference in any of the secondary outcomes between the groups. Conclusions. The P-PERSoN trial showed no difference in postoperative pulmonary complications between sugammadex and neostigmine based reversal of aminosteroid neuromuscular block, but was underpowered to show any difference due to early trial termination. The randomisation and data collection was feasible. We support the need for an adequately resourced and funded randomised controlled trial to address this important clinical question.